Political crisis and the emergence of the “diffuse hatred violence”. - Silva, Ana Paula (Universidade Estadual Paulista / UNESP, 2018)
The concept of diffuse hatred violence is defined as a multiplicity of acts related to the intolerance which has various motivations, engendered as consequence of the political crisis and citizenship deterioration. To approach this theme, it is intended to develop a theoretical and a historical dimension. The first one is based on the Hannah Arendt’s political philosophy concept: that the violence is the opposite of power, which is understood as concerted political action. This conception contributes to the understanding that this type of violence can be characterized by the construction of destructive authoritarianism which is motivated, in the modern experience, by the fear of freedom (FROMM, 1964). Besides, the arendtian axiom is reinforced later by Michel Wieviorka (2013) in the methodological differentiation that he establishes between social conflict and violence, although the author does not use the Arendt’s theory. This theoretical reflection enables to build the bridge between the capitalism historical transformations and the diffuse hatred violence. The historical perspective is also important because it updates the debate initiated with Arendt and Fromm, which have the barbarities of the Nazism as reference that were committed in a moment of excessive concentration of political, economic and ideological powers in the hands of the State. In this sense, it is argued that the multiple and diffuse character of violence is related to the fragmentation of flexible capitalism, in which the state no longer has the strength that has made homogenous a discourse and a national identity.